Media, Politics and Democracy: A Critical Perspective - Ekmel Geçer (Erciyes University, 2018)
This article, mostly through a theoretical background, focuses on general debates of democracy, media and politics. Giving insights regarding overall perspectives of democracy, media-democracy and politics relationship, the study tries to demonstrate the view of this interaction and how media should function in a democratic development. At the end, again to have a clearer point of view, this article tackles construction of the news stories as being matter of structuring agendabuilding, public opinion and political perspectives through the news media. Here particularly media and democracy relationship will be tried to be examined giving the importance of the media courses for democracy to function in a proper way. While examining the press and politics linkage as being the main actors to set up the daily agenda and a social consensus; the role of the media in shaping the public opinion and the ideology both through external or/and internal (institutional) motives have been tried to be discussed to better debate the media problems and examine their relationship with the politics especially in Turkey.